2010
DOI: 10.1103/physrevb.82.140501
|View full text |Cite
|
Sign up to set email alerts
|

Fermi surface and electronic homogeneity of the overdoped cuprate superconductorTl2Ba2CuO6+δas revealed

Abstract: We report a quantum oscillation study of Tl 2 Ba 2 CuO 6+␦ for two different doping levels ͑T c = 10 and 26 K͒ and determine the Fermi-surface size and topology in considerable detail. Our results show that Fermi-liquid behavior is not confined to the edge of the superconducting dome and is robust up to at least 0.3T c max . Superconductivity is found to survive up to a larger doping p c = 0.31 than in La 2−x Sr x CuO 4 . Our data imply that electronic inhomogeneity does not play a significant role in the loss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
77
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 28 publications
16
77
0
1
Order By: Relevance
“…The alternative is to fit the data to a series of appropriate geometrical harmonics. This latter approach works well when the Fermi surface is relatively simple and only has small deviations from a sphere or a two dimensional tube and only a small number of harmonics are required (for example, SrRu 2 O 4 [27] or Tl 2 Ba 2 CuO 6+δ [28,29]). …”
Section: Lafepomentioning
confidence: 99%
“…The alternative is to fit the data to a series of appropriate geometrical harmonics. This latter approach works well when the Fermi surface is relatively simple and only has small deviations from a sphere or a two dimensional tube and only a small number of harmonics are required (for example, SrRu 2 O 4 [27] or Tl 2 Ba 2 CuO 6+δ [28,29]). …”
Section: Lafepomentioning
confidence: 99%
“…We find further evidence for the mechanism proposed here from another cuprate superconductor. Quantum oscillation measurements showed that an overdoped Tl 2 Ba 2 CuO 6+d (Tl2201) has a much more homogenous chemical potential, 42 because the dopants in Tl2201 are farther from the copper oxide plane than the dopants in LSCO and BSCCO.…”
Section: Effectmentioning
confidence: 99%
“…It has become one of the most extensively studied materials in the cuprate family, having well-identified critical points [7] and electronic orders [8][9][10][11][12]. While quantum oscillations and transport have been thoroughly studied in underdoped YBCO [13][14][15], similar measurements cannot be extended to the overdoped regime in the same material, despite having been successfully used to study the Fermi surface of a different cuprate, Tl 2 Ba 2 CuO 6+x (Tl-2201) [16,17]. This is due to the fact that chemical doping in YBCO can only achieve a maximum hole concentration of 19.4% with oxygen tuning, and up to 22% with calcium substitution [18].…”
mentioning
confidence: 99%